(untitled) - World Health Organization (WHO) (Switzerland, 2006)
This manual is intended to guide the coordinated implementation of regular, systematic, large-scale interventions that provide anthelminthic drug treatment as a core component of the joint and synergic control of helminthic diseases such as lymphatic filariasis, onchocerciasis, schistosomiasis and soil-transmitted helminthiasis. The manual focuses mainly on antihelminthic treatment, but other drugs used to eliminate other agents can be potentially associated to those mentioned in the manual; as a reference trachoma control through the SAFE strategy, combining drug treatment with hygiene and environmental management, can be associated to helminth control interventions to boost the overall health of affected communities. The greatest challenge is to extend regular anthelminthic drug coverage as a public health intervention to reach all individuals at risk of the morbidity caused by helminthic infections. Preventive chemotherapy should therefore begin early in life, and every opportunity should be taken to reach at-risk populations. This manual advocates much greater coordination among disease control interventions . Because such large numbers of people are affected, and are often difficult to reach, it also stresses the need to make the best use of all existing drug distribution channels to deliver anthelminthic drugs, and aims at encouraging programme managers to find other innovative means of reaching those in need in a sustainable manner.
Keywords: Helminthiasis,Helminthiasis,Anthelmintics,Bệnh giun sán,Bệnh giun sán,Thuốc trừ giun sán; Prevention and control,Drug therapy,Administration and dosage,Phòng, chóng và kiểm soát,Thuốc trị liệu,Điều trị và liều lượng